Analisis Sistem Manajemen Risiko pada Operasional Usaha Angkringan Ojo Mumet Cibeber-Cilegon - Aisah Nurmala; Sayful Hidayat; Kayis Jabir Malik Alwan; Ryan Lukmanda (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to evaluate the risk management system implemented in the operations of Angkringan Angkojo in Cilegon, Banten. As a small and medium-sized enterprise (SME) in the culinary sector, Angkringan Angkojo faces various operational challenges, such as financial risks, supply chain issues, customer satisfaction, and weather-related impacts. The risk management system plays a crucial role in identifying, analyzing, and mitigating potential risks that could affect the sustainability of the business. The research employs a qualitative approach, with data collected through direct observation, interviews with the business owner, and analysis of related documents. The analysis process follows the stages of risk identification, impact assessment, and mitigation strategies implementation. The findings reveal that the primary risks include delays in the supply of raw materials, a decrease in customer numbers due to bad weather, and competition from similar businesses. Mitigation efforts include partnerships with local suppliers, providing adequate shelter facilities, and optimizing digital marketing through social media to attract more customers.